2022
DOI: 10.1002/suco.202200759
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and damage modeling research on compression‐shear behavior of carbon fiber recycled aggregate concrete

Abstract: The application potential of recycled aggregate concrete has been realized with the development and utilization of waste concrete. Fibers are added to concrete made with recycled coarse aggregate to enhance its mechanical properties and broaden its application possibilities. Additionally, in practical applications, parts of structural elements are frequently under compressionshear stress. As a result, the normal stress ratio k (k = σ/f cu , where σ is axial compressive stress, and f cu is concrete cube compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The rock and concrete mechanic (RMT-301), developed by the Wuhan Institute of Geotechnical Science, Chinese Academy of Sciences, with a load capacity of 1500 and 500 kN in axial directions and lateral directions, respectively, was subjected to compression tests, tensile tests, direct shear tests, and compression-shear tests. 18 Therefore, a combined compression-shear test system can be created by simultaneously using the axial actuator and lateral actuator. The shear force, axial force, shear displacement, and axial displacement in the test system can all be automatically recorded by the computer.…”
Section: Shear Load Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The rock and concrete mechanic (RMT-301), developed by the Wuhan Institute of Geotechnical Science, Chinese Academy of Sciences, with a load capacity of 1500 and 500 kN in axial directions and lateral directions, respectively, was subjected to compression tests, tensile tests, direct shear tests, and compression-shear tests. 18 Therefore, a combined compression-shear test system can be created by simultaneously using the axial actuator and lateral actuator. The shear force, axial force, shear displacement, and axial displacement in the test system can all be automatically recorded by the computer.…”
Section: Shear Load Systemmentioning
confidence: 99%
“…Fibers are typically added to concrete to improve its properties. 6,[18][19][20] Indeed, as compared to unreinforced concrete, fiber-reinforced concrete is characterized by improved resistance to cracking, tensile strength, flexural strength, shear strength, ductility, and toughness. 21 Furthermore, adding fiber to RAC can not only improve the crack resistance, impact resistance, and ductility of concrete but also make up for some defects of RCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all RA is sourced from the crushing of unused concrete components, 14,15 a distinction is usually drawn between the behavior of the coarse and the fine fractions: The coarse fraction is composed of particles >4 mm that consist of NA and adhered mortar 16,17 . Compared to coarse NA, the presence of adhered mortar in coarse RA lowers its density, raises its water absorption levels, and lessens its adherence within the new cementitious concrete matrix when used as an aggregate 18,19 . All these aspects decrease concrete workability, strength, and elastic stiffness 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, according to previous studies, the material properties of RAC are different from natural aggregate concrete (NAC). 8 It is shown that: recycled coarse aggregate (RCA) usually has greater porosity, water absorption, and lower strength at the same ratio; RAC has a low modulus of elasticity and greater dispersion of parameters [9][10][11] ; RAC is more brittle than NAC 12,13 ; RAC has a damage evolution is more complex than that of NAC. 14 The above research proved that there are some differences in the properties of RAC compared with NAC after crushing.…”
Section: Introductionmentioning
confidence: 99%